Pengaruh Literasi Digital Terhadap Pelaku UMKM dalam Pemasaran Syari’ah - Ghina Sevty Jou Ananda; Ahsan Putra Hafiz; Fauzan Ramli (Asosiasi Riset Ilmu Manajemen Kewirausahaan dan Bisnis Indonesia, 2024)
The aim of this research is to determine the influence of Digital Literacy in increasing sales marketing for UMKM in Telanaipura, Jambi City. This research is a type of qualitative research. Data collection techniques were through observation and interviews conducted by researchers with UMKM actors as a sample of which 16 people were interviewed. The results of this research show that the digital literacy strategy carried out by UMKM actors in Telanaipura , Jambi City is in the form of marketing through social media and also e-commerce applications such as grabfood and gofood. The impact of Digital Literacy in increasing company profits is not very significant because their understanding of digital literacy is still lacking. However, Digital Literacy-based marketing has a positive impact on the sustainability of UMKM in Telanaipura, Jambi City. With Digital Literacy, UMKM can promote their businesses more easily and reach consumers more widely. Digital Literacy also makes it easier for consumers to buy food and drinks without having to come directly to UMKM outlets. This can provide comfort and convenience for consumers so that it also has a good impact on UMKM.